STRUCTURAL CAPITAL PHENOMENOLOGY IN ACHIEVING HIGHER EDUCATION VISION - Mohammad Darul Fadli, Uus; Jamaludin, Asep; Rinta Suhardi, Agatha (International Journal of Psychosocial Rehabilitation, 2020)
University structural capital is part of intellectual capital that examines intangible capital owned by the University. Structural capital of higher education plays an important role in forming good universities that will build universities that are superior and able to compete or collaborate to develop higher education systems and build knowledge for the various needs of human life. This research uses the phenomenology method by examining the experiences of the leaders of Buana Perjuangan University (UBP) Karawang. There were 9 respondents sampled in this study consisting of the chancellor, vice-chancellors, deans and lecturers. This research focuses on the meaning of the respondents' experience in leading and managing the university's structural capital to become a competitive tertiary institution in accordance with the established vision, able to develop academics, research, community service, institutions, student affairs and establish good relations with external parties. The results showed that UBP Karawang has successfully carried out planning, organizing, leading and controlling the organizational structure of Idiosyncratic Structural Capital, Structural Capital for residual organizations, Structural Capital for Organizational Organizations and Structural Capital for Generic Organizations in all lecturers and education staff to become university knowledge so that they can produce universities higher education competition that enables the achievement of a vision in accordance with the period of performance. This research provides information that the management of structural capital in higher education is very important to build university knowledge that can be a guide in achieving the vision of higher education.